A Brief Analysis and Interpretation on Arithmetic Operations of Fuzzy Numbers - Mukherjee, Asesh Kumar; Gazi, Kamal Hossain; Salahshour, Soheil; Ghosh, Arijit; Mondal, Sankar Prasad (Results in control and optimization, 2023)
Fuzzy set theory is a generalized form of crisp set theory where elements are binary inclusion forms. In fuzzy set, it differs with degree of membership for every element in the set. There are several strategies for arithmetic operations on fuzzy numbers. Previous studies show that there are many approaches, such as the α−cut technique, extension principle, vertex method, etc., to execute arithmetic operations on fuzzy numbers. In this study we perform details analysis and interpretation on arithmetic operations based on the α−cut method in a new way.